A Study on the Attributes of the Productivity–Liquidity Relationship at the Firm Level. Issue 4 (2nd October 2021) - Tiruvengadam, Naveen; Elizondo-Noriega, Armando; Beruvides, Mario G.
Abstract: This study explores the various attributes of the direct relationship between firm-level productivity, measured by total factor productivity, and liquidity, determined by the cash conversion cycle, without the intermediating effect of firm profits. For this objective, panel data is employed to understand the existence, linearity, directionality, type, and seasonality (or its absence) of such a relationship for firms of all sizes across several sampled industries. The results demonstrate that the relationship exists to a considerable extent, is bi-directional, predominantly linear with non-linearity observed in the case of revenue-wise large firms, and primarily negative and seasonal.